DIFFERENTIATED METHOD OF TEACHING WHEN STUDYING A FOREIGN LANGUAGE AND ORGANIZING INDEPENDENT WORK OF STUDENTS (Scientific journal of the Fergana State University, 2024)
The article reveals the importance of differentiated learning in organizing students' independent work, which attracts the attention of teachers throughout the country, which helps students meet the requirements of state educational standards, and enables teachers to become more competent in teaching. planning, which is important for each student in his presentation of the material being studied, regardless of the level of readiness.